Place of Delivery Associated With Postnatal Care Utilization Among Childbearing Women in Zambia - Chungu, Charles; Makasa, Mpundu; Chola, Mumbi; Jacobs, Choolwe Nkwemu (Frontiers in Public Health, 2018)
Objective Postnatal care (PNC) utilization is critical to the prevention of maternal morbidity and mortality. Despite its importance, the proportion of women utilizing this service is still low in Zambia. We investigated if place of delivery was associated with PNC utilization in the first 48 h among childbearing women in Zambia. Methods Data from the 2013/14 Zambia Demographic and Health Survey for women, aged 15–49 years, who reported giving birth in the 2 years preceding the survey was used. The data comprised of sociodemographic and other obstetric data, which were cleaned, recoded, and analyzed using STATA version 13 (Stata Corporation, College Station, TX, USA). Multivariate logistic regression was used to examine the association of place of delivery and other background variables. Results Women who delivered in a health facility were more likely to utilize PNC in the first 48 h compared to those who did not deliver in a health facility: government hospital (AOR 7.24, 95% CI 4.92–11.84), government health center/clinic (AOR 7.15 95% CI 4.79–10.66), other public sector (AOR 23.2 95% CI 3.69–145.91), private hospital/clinic (AOR 10.08 95% CI 3.35–30.35), and Mission hospital/clinic (AOR 8.56 95% CI 4.71–15.53). Additionally, women who were attended to by a skilled personnel during delivery of the baby were more likely to utilize PNC (AOR 2.30, 95% CI 1.57–3.37). Women from rural areas were less likely to utilize PNC in the first 48 h (AOR 0.70, 95% CI 0.53–0.90). Conclusion Place of delivery was found to be linked with PNC utilization in this population although access to health care is still driven by inequity-related dynamics and imbalances. Given that inequity stresses are heaviest in the rural and poor groups, interventions should aim to reach this group. Significance The study results will help program managers to increase access to health facility delivery and direct interventional efforts toward the affected subpopulations, such as the young and rural women. Furthermore, results will help promote maternal health education on importance of health facility delivery and advise policy makers and program implementers.